Differences in patient and caregiving partner responses to individual items on the FACIT-COST questionnaire. Issue 28 (1st October 2022) - Rivers, Zachary; Shankaran, Veena; Porter, Laura S; Langer, Shelby
Abstract : 183 Background: The financial impacts of cancer diagnosis and treatment extend beyond patients to affect intimate partners. Understanding how both members of the dyad experience financial toxicity (FT) can help inform dyadic interventions to address FT. We compare patient and partner responses to items on the Functional Assessment of Chronic Illness Therapy (FACIT)-COST, a patient-reported outcome measure of cancer-related financial distress. Methods: Adult patients with stage II-IV breast, lung, or colorectal cancer and their spouse/ cohabiting partner independently completed the 11-item FACIT-COST. Correlations between responses by both members were calculated using Pearson's correlation coefficient. Results: There were 336 dyads (median patient age 53, 45% stage IV, 84% white) included in the analysis. Both members of the dyad had similar FT experiences in 74% of cases (26% and 48% reported FT and no FT respectively) while 26% diverged in their experience of FT. Responses to items 3, 6, 7, 10, and 11 (Table) were highly correlated (r > 0.6) while responses to questions 4 (I feel I have no choice about the amount of money we spend on care) and 5 (I am frustrated that I cannot work or contribute as much as I usually do) were weakly correlated (0.3 > r > 0), with patients generally reporting worse scores than partners on these items. Conclusions: Within-couple correlation between FACIT-COST items varies, with multiple responses weakly correlated. Future research should assess the impact of this variation on psychosocial functioning and explore approaches to facilitate dyadic communication around this important issue.FACIT-COST item number and question Patient, M (SD) Partner, M (SD) r Highest agreement 11. I feel in control of my financial situation 2.09 (1.39) 2.26 (1.33) 0.78 6. I am satisfied with my current financial situation 1.96 (1.41) 2.03 (1.37) 0.76 7. I am able to meet my monthly expenses 2.74 (1.31) 2.96 (1.22) 0.73 10. Treatment has reduced my satisfaction with my present financial situation 2.4 (1.47) 2.87 (1.22) 0.68 3. I worry about the financial problems I will have in the future as a result of illness or treatment 2.29 (1.35) 2.62 (1.34) 0.63 Lowest agreement 5. I am frustrated that I cannot work or contribute as much as I usually do 2.45 (1.51) 3.19 (1.23) 0.28 4. I feel I have no choice about the amount of money we spend on care 2 (1.47) 2.52 (1.51) 0.09